1994
DOI: 10.1042/bj3030967
|View full text |Cite
|
Sign up to set email alerts
|

The microsomal epoxide hydrolase has a single membrane signal anchor sequence which is dispensable for the catalytic activity of this protein

Abstract: The microsomal epoxide hydrolase (mEH) catalyses the hydrolysis of reactive epoxides which are formed by the action of cytochromes P-450 from xenobiotics. In addition it has been suggested that mEH might mediate the transport of bile acids. For the mEH it has been shown that it is co-translationally inserted into the endoplasmic reticulum. Here we demonstrate that the N-terminal 20 amino acid residues of this protein serve as its single membrane anchor signal sequence and that the function of this sequence can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Its members are, on average, 100 (bacterial), 120 (fungal), and 150 (higher eukaryotes) amino acids longer than most other epoxide hydrolases (Table 2), which is mainly due to a large N-terminal extension. The mammalian and insect epoxide hydrolases of this group are membrane bound by an N-terminal membrane anchor (20). The fungal and bacterial epoxide hydrolases of this group do not contain this membrane anchor and are therefore probably soluble.…”
Section: Resultsmentioning
confidence: 99%
“…Its members are, on average, 100 (bacterial), 120 (fungal), and 150 (higher eukaryotes) amino acids longer than most other epoxide hydrolases (Table 2), which is mainly due to a large N-terminal extension. The mammalian and insect epoxide hydrolases of this group are membrane bound by an N-terminal membrane anchor (20). The fungal and bacterial epoxide hydrolases of this group do not contain this membrane anchor and are therefore probably soluble.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, release of VKOR from the ER membrane required detergent (squares). The detergent concentrations used were also shown to release the two ER integral membrane proteins mGST and mEH, which are both anchored to the membrane by one transmembrane domain (28,29). This shows that some of the VKOR protein components are firmly attached to the ER membrane.…”
Section: Association Of Cytosolic Gsts and Vkor With The Er Membrane-mentioning
confidence: 91%
“…Hydropathy analysis has suggested the presence of 4 (11) or 6 (31) domains that integrate into the membrane. Other studies, however, have suggested the existence of only a single transmembrane domain comprising amino acids 4 -20 (32,33). The cDNA of mEHt was transfected into COS-7 cells, and analysis of total protein indicated the synthesis of a protein at approximately the same level of expression as the other derivatives in this study, with the predicted decrease in molecular weight (Fig.…”
Section: Fig 4 Expression Of Meh and Meh Derivatives In Cos-7 Cellsmentioning
confidence: 97%
“…Hydropathy analysis indicates the presence of a hydrophobic N-terminal region as well as several additional domains that could integrate into the membrane (11,31). Studies using truncated mEH suggested that mEH has only a single transmembrane domain, based on the results of alkaline extraction of membranes containing mEH or the truncated derivative (32). The expression of this truncated derivative, however, was only 5% of the level observed for mEH in BHK cells, and the authors failed to point out that approximately 40% of the truncated mEH appeared to be resistant to this extraction procedure, thereby leaving the conclusion of this study open to question.…”
Section: Discussionmentioning
confidence: 99%